2018
DOI: 10.1172/jci.insight.94463
|View full text |Cite
|
Sign up to set email alerts
|

Pro-resolving mediators promote resolution in a human skin model of UV-killed Escherichia coli–driven acute inflammation

Abstract: While the treatment of inflammatory disorders is generally based on inhibiting factors that drive onset of inflammation, these therapies can compromise healing (NSAIDs) or dampen immunity against infections (biologics). In search of new antiinflammatories, efforts have focused on harnessing endogenous pathways that drive resolution of inflammation for therapeutic gain. Identification of specialized pro-resolving mediators (SPMs) (lipoxins, resolvins, protectins, maresins) as effector molecules of resolution ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 59 publications
0
67
0
Order By: Relevance
“…Additionally, our functional findings were accompanied by an increased expression of several important proresolving receptors (GPR32, ChemR23, ALX, and GPR18), strengthening our line of argumentation. These receptors have just recently been shown to be involved in inflammation resolution in a human skin blister model (55). Ultimately, we monitored important CYP, 15-LOX, and COX pathway markers under treatment of human MΦ with zyA, with and without SH42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our functional findings were accompanied by an increased expression of several important proresolving receptors (GPR32, ChemR23, ALX, and GPR18), strengthening our line of argumentation. These receptors have just recently been shown to be involved in inflammation resolution in a human skin blister model (55). Ultimately, we monitored important CYP, 15-LOX, and COX pathway markers under treatment of human MΦ with zyA, with and without SH42.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned findings might lead to novel treatment opportunities, as polymorphisms in the 15-LOX pathway have been linked to the development of asthma, arthritis, and atherosclerosis in humans. Products of this pathway (MaR1 and LXA 4 ) have been described in a human skin blister model (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…MaR1 is produced in humans (7,(15)(16)(17)(18)(19), and its defining physiologic functions include limiting PMN infiltration in murine peritonitis, enhancing human MΦ uptake of apoptotic PMNs (16), the hallmarks of proresolving mechanisms. By controlling inflammation after surgical tissue injury, MaR1 accelerates planaria regeneration (12).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have demonstrated a lipid mediator "class switch" in the biochemical transition from inflammation to resolution, wherein early proinflammatory prostaglandins and leukotrienes are replaced by SPMs in exudates. The mechanisms of this shift in eicosanoid profile involve temporal changes in the expression, localization, and activity of key cellular enzymes such as 5-and 15-lipoxygenases (LOXs) (10)(11)(12). Once available, SPMs coordinate crosstalk between leukocytes and local cell populations, promoting an M1-M2 phenotypic transition in macrophages that is central to tissue repair (13).…”
mentioning
confidence: 99%
“…Once available, SPMs coordinate crosstalk between leukocytes and local cell populations, promoting an M1-M2 phenotypic transition in macrophages that is central to tissue repair (13). SPMs further promote resolution by positive-feedback effects on LOX activity and SPM receptor expression in leukocytes (11,12,14). Translation of these concepts into therapies for complex human diseases is the current challenge faced by investigators in this exciting, evolving field.…”
mentioning
confidence: 99%